Mucosal nanobody IgA as inhalable and affordable prophylactic and therapeutic treatment against SARS-CoV-2 and emerging variants - Li, Qi; Humphries, Fiachra; Girardin, Roxie C.; Wallace, Aaron; Ejemel, Monir; Amcheslavsky, Alla; McMahon, Conor T.; Schiller, Zachary A.; Ma, Zepei; Cruz, John; Dupuis, Alan P.; Payne, Anne F.; et al. (Frontiers in Immunology, 2022)
Anti-COVID antibody therapeutics have been developed but not widely used due to their high cost and escape of neutralization from the emerging variants. Here, we describe the development of VHH1.1, a nanobody IgA fusion molecular as an inhalable, affordable and less invasive prophylactic and therapeutic treatment against SARS-CoV-2 Omicron variants. VHH-IgA 1.1 recognizes a conserved epitope of SARS-CoV-2 spike protein Receptor Binding Domain (RBD) and potently neutralizes major global SARS-CoV-2 variants of concern (VOC) including the Omicron variant and its sub lineages BA.1.1, BA.2 and BA.2.12.1. The IgA fusion of VHH1.1 is also much more potent against Omicron variants as compared to its IgG Fc fusion demonstrating the importance of IgA mediated mucosal protection for Omicron infection. Intranasal administration of VHH-IgA1.1 prior to or after challenge conferred significant protection from severe respiratory disease in K18-ACE2 transgenic mice infected with SARS-CoV-2 VOC. More importantly, for cost-effective production, VHH-IgA1.1 produced in Pichia pastoris had comparable potency as mammalian produced antibody. Our study demonstrates that intranasal administration of VHH-IgA fusion protein produced affordably provides effective mucosal immunity against infection of SARS-CoV-2 including the emerging variants.